2002
DOI: 10.1002/ccd.10072
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous repair of abdominal aortic aneurysms using the AneuRx stent graft and the percutaneous vascular surgery device

Abstract: Endovascular exclusion of abdominal aortic aneurysms (AAAs) was developed in an effort to treat patients who were at high risk for complications following standard surgical repair. Stent grafts used for endovascular repair of AAAs require the use of large-bore sheaths and surgical exposure of the common femoral arteries (CFAs). To decrease the invasiveness of AAA repair, we attempted to perform the procedure percutaneously utilizing the Prostar XL Percutaneous Vascular Surgery Device and the preclose technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 41 publications
1
74
1
Order By: Relevance
“…Vascular complications are rare [14]. In previous studies, investigators introduced the so called "Pre-closure" technique for large-bore arteriotomies using percutaneous closure devices [7][8][9][10][15][16][17]. This technique originated from the modified percutaneous approach in 1997, which included a short incision and 3-0 suture through the fascia for safe sheath removal [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular complications are rare [14]. In previous studies, investigators introduced the so called "Pre-closure" technique for large-bore arteriotomies using percutaneous closure devices [7][8][9][10][15][16][17]. This technique originated from the modified percutaneous approach in 1997, which included a short incision and 3-0 suture through the fascia for safe sheath removal [15].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular complications using 6 Fr Perclose devices are uncommon and include failed hemostasis with hematoma, infection, pseudoaneurysm, device malfunction, or arterial thrombosis [14]. Because endovascular techniques for aortic diseases require large-bore vascular access, suture-mediated percutaneous closure has been International Journal of Cardiology 130 (2008) 251 -254 www.elsevier.com/locate/ijcard described using the "Pre-close technique" [7][8][9][10][15][16][17]. In previous studies [7,8,10,17], the Prostar XL percutaneous vascular device (Perclose, Menlo Park, CA) was used, but there is no study using the more popular and practiced suturemediated closure device, Closer-S.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-operative radiological assessment of the iliofemoral vessels is essential to assess for calcification and tortuosity with high failure rates expected for patients who are obese or who have scarred groins [3]. Just 1 year later, Howell et al [5] reported a 93% success rate in their series. The progressively improving success rates are undoubtedly a reflection of the learning curve and while we are satisfied with our results to date, these may be a reflection of the relatively small numbers included in our series.…”
Section: Discussionmentioning
confidence: 98%
“…In light of this, percutaneous EVAR (p-EVAR) techniques have been developed. Further potential advantages of p-EVAR are reductions in operating time, blood loss, time to ambulation and hospital stay [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%